Assessment of Self-Stigma, Self-Esteem, and Asthma Control: A Preliminary Cross-Sectional Study Among Adult Asthmatic Patients in Selangor, Malaysia - Ahmad, Sohail; Ismail, Ahmad Izuanuddin; Zim, Mohd Arif Mohd; Ismail, Nahlah Elkudssiah (Frontiers in Public Health, 2020)
Purpose: The elusive goal of asthma management guidelines is to achieve and maintain good asthma control in asthmatic patients. Against a background of long-term respiratory limitations when living with asthma, stigma and low self-esteem have also been identified as the social phenomenon among adult asthmatics. This study aimed to assess the levels of self-stigma, self-esteem, and asthma control, and to investigate the impact of self-stigma and self-esteem as psychosocial factors on asthma control in Malaysian adults living with asthma. Materials and Methods: In this multicenter cross-sectional study, post-ethics approval and patients' consents, 152 stable asthmatic patients (aged > 18 years old; nil cognitive disability; not diagnosed with other respiratory diseases) were recruited from four respiratory clinics in Selangor, Malaysia. The patients' socio-demographic, medical, and psychosocial (self-stigma and self-esteem) data were recorded in a pre-validated, self-designed questionnaire. All data were analyzed descriptively and inferentially (independent t-test/one-way ANOVA, and multiple linear regression) using the Statistical Package for Social Sciences (SPSS®). Results: The enrolled patients showed moderate levels of self-stigma (62.12 ± 6.44) and self-esteem (29.31 ± 3.29), and not well-controlled asthma (17.58 ± 3.99). The number of patients' visits to emergency rooms because of asthma [CI (−1.199, 0.317), p < 0.001] was the significant predictor to asthma control among all selected study variables from socio-demographic and medical data. Moreover, from psychosocial factors both self-stigma [CI (−0.367, 0.190), p < 0.001], and self-esteem [CI (−0.007, 0.033), p = 0.041] found to be the significant predictors of asthma control. Conclusion: The preliminary evidences presented in this study found that frequent emergency room visits, high self-stigma and low self-esteem in asthma patients becomes more apparent with poor asthma control. Educational interventions to reduce patients' self-stigma and improve self-esteem are needed to achieve optimal control of asthma.